The Influence of social media Facebook on The Student’s Learning Motivation of FKIP Universitas Islam Riau - Syofianis Ismail; Resy Oktadela; Erna Nawir (Lafadz Jaya Publisher, 2023)
Many people use social media as a way to connect to their friends and families and increasingly, people are using social media as a way to spread and to get information across wider networks. Many social networking sites can also be a place to share information and can become a means of getting a lot of friends and to find a mate. Among social networking that is increasingly popular are Twitter, YouTube, Blogger Facebook and many more. Facebook is one of the social networking websites that is now increasingly popular, and the number of members increase significantly in a short time. This is probably because it can make teenagers more expressive, highlight themselves, although to some extent these students may disturb their study as they may spend a lot of time on it. The concept of the theory used in this research is Communication Model of Stimulus and Response. To measure the stimulus arising from a sale effectively, required knowledge that influences a person to receive, consider the information and make a decision to buy the products. As quantitative research, this research is to measure the force between two variables, namely social media face book as an independent variable and learning motivation of students as the dependent variable. used simple regression, or often called simple regression. From t test results obtained value for the variable t - test Social Media face book 3.800 (greater than ttabel 1.984), and p value of 0.000 < 0,05), the results of this study indicate that social media facebook affect study learning motivation FKIP Universitas Islam Riau.